Aplikasi Willingness To Pay: Proksi terhadap Penentuan Harga (Model Empirik dalam Estimasi Permintaan Air PDAM Rumah Tangga di Kabupaten Banyumas) - Irma Suryani; Nurul Anwar; Sudjarwanto Sudjarwanto (EKO-REGIONAL, 2011)
The price of freshwater is still determined by PDAM, owned by local government, as a producer. It indicates that PDAM as a monopolist. It can be explained that freshwater is public goods so must be distributed equitably among the people. Thereby there is price discrimination of freshwater for costumer based on the willingness to pay (WTP). The price based on WTP can be defined as the costumer ability for paying the rate of freshwater using by household. This research are aimed to analyze WTP by utility concept on demand of freshwater used by household and determine the rate of WTP as a proxy of freshwater price paid by household. The result shows that the people have the kindness to pay costs for using freshwater trough PDAM. The rate of WTP for using freshwater is about Rp395,41/m3 and the total WTP of one household is Rp9252,59/month excluded from administered cost. Keywords:   willingnes to pay, utility, proxy